The diversity and distribution of Alpinia zerumbet clade in West Malesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Setiawan E, Ardiyani M, Miftahudin, Poulsen AD, Chikmawati T. 2022. The diversity and distribution of Alpinia Zerumbet  clade in West Malesia. Biodiversitas 23: 1734-1744. Alpinia belongs to the family Zingiberaceae and tribe Alpinioideae. One of the centres of Alpinia diversity is in Malesia, yet information regarding the taxon in this area is very limited. Furthermore, species richness and distribution in West Malesia have not been well documented particularly in respect of the taxonomical development following clade classification. The aim of the current paper is to study the morphological diversity and distribution of Alpinia Zerumbet clade in West Malesia to provide taxonomic information. Exploration was done in several locations in Java and Sumatra. Data were obtained from fresh and herbarium specimens preserved in three herbaria (BO, SING, BRUN), as well as digitally (L, E, and K). A total of 16 Alpinia species are placed in the clade of Zerumbet classified into a section, namely section Alpinia were recorded in West Malesia. They share several characters: i.e. absent or caducous secondary bracts, small or reduced lateral staminodes, and often having a petaloid and showy labellum. The highest diversity of Alpinia Zerumbet clade is recorded in the Philippines and Borneo (each has 7 species) and the lowest diversity is in Java (2 species). The most abundant habitat is in the lowlands and mountain rainforests. Most species of Alpinia Zerumbet clade are found in primary forest and secondary forest (Pinus or Agathis forest). A determination key was constructed based on information in the literature and direct observations of herbarium specimens.